Surrounded by idiots : the four types of human behavior and how to effectively communicate with each in business (and in life) - Erikson, Thomas, 1965- (St. Martin's Essentials, 2019)
A runaway bestseller in Sweden that has sold more than a million copies worldwide, Surrounded by Idiots shares a simple, revolutionary method of understanding the people around you that will change how you interact with everyone from your coworkers to your spouse. Author Thomas Erikson explains that there are four key behavior types that define how we interact with and perceive the people around us. Understanding someone<U+2019>s pattern of behavior is the key to successful communication. The so-called “idiots” in our lives are most often simply people who have a different behavior profile and style of communication. Erikson breaks down the four kinds of behavior types<U+2015>Reds who are dominant and commanding, Yellows who are social and optimistic, Greens who are laid back and friendly, and Blues who are analytical and precise<U+2015>and explains how to identify and interact with each type of person. Instead of being bogged down with overly technical categorizations, the simple four-color system allows you to speedily identify a friend or coworker and adjust how you speak and share with them. Surrounded by Idiots is full of practical information for interacting with people based on their color, including the strengths and weaknesses of all the profiles, how to give positive and negative feedback to each, and the best way to word an email when writing to someone with a different profile.